A pilot project to evaluate patient preferences in osteoporosis. - Cranney, Anne B. (University of Ottawa (Canada), 1998)
The study objective was to develop and evaluate the psychometric properties of preference-based measures in osteoporosis. Preference scenarios were constructed for marker health states associated with osteoporosis using the feeling thermometer. The reliability, validity and sensitivity to change of these measures and the standard gamble were evaluated in 42 women from four different patient subgroups. The four subgroups of women included women commencing hormone replacement, and women with recent wrist, vertebral or hip fractures. The reason for looking at different groups of women was to establish the feasibility of eliciting preferences in women with varying degrees of osteoporosis. Also, for cost-effectiveness analyses in osteoporosis, estimates of quality of life are required for the four different subgroups. The validity and sensitivity to change of the feeling thermometer and standard gamble were compared with the Health Utilities Index (HUI) and SF-36. All subgroups were reassessed 2-3 months following their first interview. (Abstract shortened by UMI.)
Keywords: Health Sciences, Medicine and Surgery.